Zonas de amortiguamiento entendidas comoun proceso de difusión espacial de una innovación - Gierhake, Klaus; Justus Liebig University Giessen (My University, 2002)
The study analyses perspectives and restrictions to integrate biodiversity as an issue in public administration and in one of its principle instruments, development plans. This is done on the basis of two case studies, a Bolivian and a Peruvian province, each of them at the eastern slope of the Andes. These two provinces, Florida (Dept. Sta. Cruz) and Manu (Dept. Madre de Dios) share some common basic characteristics: both were located in one of the national development corridors for a certain time, resulting in the attraction of migrants from other parts of the countries. At present they are periferical regions in the overall national/regional development context, a National Park is covering important parts of each province. Bolivia and Peru adopted different approaches to work on environment and biodiversity in the respective systems of public administration. In the case of Bolivia all competence for multidisciplinary planning, with a decisive focus on environmental topics, were concentrated in only one national Ministry. A comparative organisation structure was reproduced on the regional level. In contrast, in Peru the competencies for environment were distributed to all sectorial Ministries, reflecting a basic policy decision to facilitate private investment interpreted as a primary tool for development, especially in the Amazon region. However, a centralisation of decision making on the central state level has taken place in this process. Development plans represent s strategic instrument to transform basic institutional competencies into concrete activities. Bolivia has established a framework of national planning, which defines the responsibilities of each planning level, a general condition that probably can explain the quality of the development concept presented by the Florida province. In Peru, several basic laws with comparatively far reaching goals for the protection and sustainable use of biodiversity were approved, however they are lacking of implementing orders ('decretos'). As a result, these laws still don´t have produced significant impacts on the operational level. It is important to keep in mind, that no general framework on national / regional planning exist in Peru. From a conceptual point of view, the Florida Development Plan offers a good analysis of the internal / external effects producing impacts on the development perspectives of the province, as well as proposals taking into account the localisation of the province in the regional / national context and the needs of conservation and sustainable development patterns for the Amber National Park. In comparison, the Manu Development Plan shows certain conceptual deficits, for example regarding the concrete analysis of the distribution of competencies in public administration and the possibilities of decision taking in the Province itself, the perspectives and limitation of the existing technical infrastructure and the present spatial relations of the regional economy. Conservation and sustainable use of biodiversity is mentioned as an objective, but the way the activities are planned do not necessarily result in the fullfillment of these objectives.
Keywords: Raumordnung; Pufferzonen; Innovation; Peru; Ecuador; ddc:910